Efficacy of indirect elisa using crude soluble entamoeba histolytica antigen for the diagnosis of amoebic liver abscess - Khairul Nissa, Saidun (Universiti Sains Malaysia, 2009)
Amoebiasis is an infection of a parasitic protozoan, Entamoeba histolytica. There are two types of amoebiasis, intestinal amoebiasis and extraintestinal amoebiasis. Ten percent of world population was infected by amoebiasis, and high mortality rate was recorded due to amoebic liver abscess (ALA) second after malaria. Although it is treatable, it is usually too late when detected. Many clinical tests and researches are underway to improve the diagnosis of amoebic liver abscess. In this study, the efficiency of Indirect ELISA using crude soluble antigen of E. histolytica for the diagnosis of ALA was investigated. The serum samples used in this study were tested with Indirect Haemaaglutination Assay (IHA) for ALA antibodies. The crude soluble protein was produced from whole cell lysate by sonication. The concentration of the protein measured by Bradford assay was 5839.I f..Lg/ml. The assay was optimized prior testing the efficacy. The optimum concentration of the antigen was 20 f..Lg/mL, I :25 and I :500 were the optimum dilutions of primary and secondary antibodies, respectively. Cut-Off Value (COV) that has been determined from 30 IHA negative ALA serum samples readings using Indirect ELISA was 0.5677. Optical density (OD) reading of the serum sample tested with Indirect ELISA that less than this point was regarded as negative. The sensitivity and specificity of the assay using crude soluble antigen were 8I.3% and 96.7%., respectively.